2017
DOI: 10.1007/s10530-017-1415-3
|View full text |Cite
|
Sign up to set email alerts
|

Getting invasive species on the political agenda: agenda setting and policy formulation in the case of ash dieback in the UK

Abstract: This study reviews how the issue of ash dieback has been placed on the political agenda in the UK, a country where the disease has affected one of the largest national extents, thus representing a particularly severe case. Comparisons are made between how the scientific community framed the ash dieback threat and the resulting response strategy and how both the media and the British government framed the problem. Representing one example of media framing, the study analyses one British newspaper's coverage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Nelson (2007) considered the impact of the Canadian mountain pine beetle epidemic on forest policy, noting that such an event could potentially form a policy window by attracting public attention and mobilising political will. Whilst Potter et al (2013) describe some substantive change in policy structures and processes in response to ash dieback in the UK (see also Mackay et al 2017), Nelson (2007) concluded that the vested economic and political interests in forestry acted to significantly constrain policy development in Canada in response to mountain pine beetle outbreaks.…”
Section: Governancewhat Are the Issues And Who Should Act?mentioning
confidence: 99%
“…Nelson (2007) considered the impact of the Canadian mountain pine beetle epidemic on forest policy, noting that such an event could potentially form a policy window by attracting public attention and mobilising political will. Whilst Potter et al (2013) describe some substantive change in policy structures and processes in response to ash dieback in the UK (see also Mackay et al 2017), Nelson (2007) concluded that the vested economic and political interests in forestry acted to significantly constrain policy development in Canada in response to mountain pine beetle outbreaks.…”
Section: Governancewhat Are the Issues And Who Should Act?mentioning
confidence: 99%
“…ADF and other pests of Fraxinus species. Although regulations are in place to prevent the introduction and spread of forest pests via transport and trade (see reference16 ), they should be continuously updated with science-based knowledge.In North America, both EAB and ADF appear in the Phytosanitary Alert System of North American Plant Protection Organization (NAPPO) (www.pestalert.org), but ADF exists only as an emerging pathogen because it is not yet present in North America. Here, classifying ADF as a "regulated pest" could help preventing the introduction of ADF into North America.In Europe, EAB is listed in the A2 List of the European Plant Protection Organization (EPPO) for pests recommended for regulation (www.eppo.int).…”
mentioning
confidence: 99%